LEGAL EDUCATION IN MALAYSIA: THE EFFECT OF APPLYING VISUAL MIND/ PROCESS MAPPING AND FLOWCHARTS TO ENHANCE THE CIVIL PROCEDURE STUDENTS’ UNDERSTANDING - Che Audah Hassan; Rahmawati Mohd Yusoff; Azhani Arshad; Syuhaeda Aeni Mat Ali; Ummi Hani’ Maso’od (Journal of Islamic, Social, Economics and Development, 2024)
In Malaysia, one of the core courses in the body of knowledge for law programs in MQA Programme Standards is the procedural course, Civil Procedure. This course offers the students the knowledge and practical skill in applying and implementing procedural law in conducting civil action at the court. This course is considered ‘dry’ in nature, which the students felt and showed difficulties visualising the process. Thus, the authors apply visual learning techniques such as mapping and flowcharts that enable students to visualise the court proceeding. This delivery technique aims to present information that suits the student's interest, enhance the law students’ understanding of law subjects and promote effective teaching and learning by integrating mind/process mapping and flowchart techniques. This research was undertaken to analyse the effect of this delivery and learning approach on civil procedure students by a quasi-experimental method. A total of 63 law students of the Faculty of Law at Universiti Teknologi MARA, Malaysia using convenience sampling which are those who attended and participated in a lecture of 14 weeks. During the intervention period, these students received basic knowledge of civil procedure using mind/ process mapping and flowchart techniques. The data collected and analysed included the final examination paper, the student’s results and the summative final examination. The study found that using mind/ process mapping techniques as a learning strategy has significantly improved their understanding of the core substance with the ability to analyse and apply it on a summative examination at the end of a course and for life-long learning.